The Impact of Oil Viscosity and Fuel Quality on Internal Combustion Engine Performance and Emissions: An Experimental Approach - Milton Garcia Tobar; Kevin Pinta Pesantez; Pablo Jimenez Romero; Rafael Wilmer Contreras Urgiles (Lubricants)
The automotive industry faces increasing challenges due to fuel scarcity and pollutant emissions, necessitating the implementation of strategies that optimize engine performance while minimizing the environmental impact. This study aimed to analyze the influence of oil viscosity and fuel quality on the engine performance and pollutant emissions in an internal combustion engine. A Response Surface Methodology (RSM)-based experimental design was employed. Three oil viscosity levels (SAE 5W-30, 10W-30, and 20W-50) and three fuel quality levels (87, 92, and 95 octane) were evaluated using a Chevrolet Grand Vitara 2.0L (General Motors, Quito, Ecuador) tested on a dynamometer. The oil grades were selected to represent a practical range of viscosities commonly used in commercial vehicles operating under local conditions. The results indicate that using lower-viscosity oil (SAE 5W-30) increased the engine power by up to 6.25% compared to when using SAE 20W-50. Additionally, using higher-octane fuel led to an average power increase of 1.49%, attributed to improved combustion stability and the ability to operate at a more advanced ignition timing without knocking. The emissions analysis revealed that high-viscosity oil at high RPMs increased CO2 emissions to 14.4% vol, whereas low-viscosity oil at low RPMs reduced CO2 emissions to 13.4% vol. Statistical analysis confirmed that the engine speed (RPM) was the most influential factor in emissions (F = 163.11 and p < 0.0001 for CO2; F = 247.02 and p < 0.0001 for NOx), while fuel quality also played a significant role. These findings suggest that optimizing the oil viscosity and selecting the appropriate fuel can enhance engine efficiency and reduce emissions, thereby contributing to the development of more sustainable automotive technologies. Future research should explore the use of ultra-low-viscosity lubricants (SAE 0W-20) and assess their long-term effects on engine wear.